Anesthetic complications in dogs undergoing hepatic surgery: cholecystectomy versus non‐cholecystectomy. (21st November 2013) - Burns, Brigid R; Hofmeister, Erik H; Brainard, Benjamin M
Abstract Objective To determine if dogs that undergo laparotomy for cholecystectomy suffer from a greater number or magnitude of perianesthetic complications, including hypotension, hypothermia, longer recovery time, and lower survival rate, than dogs that undergo laparotomy for hepatic surgery without cholecystectomy. Study design Retrospective cohort study. Animals One hundred and three dogs, anesthetised between January 2007 and October 2011. Methods The variables collected from the medical record included age, weight, gender, surgical procedure, pre‐operative bloodwork, American Society of Anesthesiologists (ASA) status, emergency status, total bilirubin concentration, anesthetic agents administered, body temperature nadir, final body temperature, hypotension, duration of hypotension, blood pressure nadir, intraoperative drugs, anesthesia duration, surgery duration, time to extubation, final diagnosis, days spent in the intensive care unit (ICU), total bill, survival to discharge, and survival to follow‐up. Results No significant difference in body temperature nadir, final temperature, presence of hypotension, duration of hypotension, blood pressure nadir, the use of inotropes, or final outcome was found between dogs undergoing cholecystectomy and dogs undergoing exploratory laparotomy for other hepatic disease. Dogs that had cholecystectomy had longer anesthesia durations and longer surgery durations than dogs that did not have cholecystectomy. No significant differences existed for temperature nadir (34.8 versus 35.3 °C; non‐cholecystectomy versus cholecystectomy), final temperature (35.6 versus 35.9 °C), time to extubation (30 versus 49 minutes), duration of hypotension (27 versus 21 minutes), or MAP nadir (56 versus 55 mmHg). Hypotension occurred in 66% and 74% and inotropes were used in 64% and 53%, for non‐cholecystectomy and cholecystectomy patients, respectively. Conclusions and clinical relevance Dogs that underwent cholecystectomies did not suffer a greater number of anesthesia complications than did dogs undergoing hepatic surgery without cholecystectomies.